Perluasan Kerja Sama Shanghai Cooperation Organization (SCO) Dalam Pandangan Teori Geopolitik McKinder - Iqbal Ramadhan (Frequency of International Relations (FETRIAN), 2020)
Abstract In the modern world politics, China has become prominent actor in International Relations Studies. This country emerges as one of world greatest economy. Sustaining its growing economy needs a lot of supports. One of them is energy. Previously, China is a member of Shanghai Cooperation Organization (SCO), an institution that consists several states from Central Asia. China expands its cooperation through SCO by developing strategic cooperation in energy sector. From this cooperation, China will gain energy necessities from their Central Asia partners. By developing this strategic cooperation, China also receives geopolitical advantage. This article aims to analyse China’s geopolitical advantage from the expanding of their cooperation in SCO. The author uses theory of classical geopolitics from McKinder (Heartland Theory) and several geopolitical concepts. The conclusion of this paper is China has a geopolitical advantage due its position in the circle of Heartland, but also from the benefit of its cooperation who try to accommodate China and Central Asian countries’ interest in energy sector. Keyword: geopolitics, McKinder Theory, China, Shanghai Cooperation Organization